Pengaruh Pemahaman Ajaran Agama Islam Terhadap Kualitas Moral Remaja - Agus Budiman; Taufik Rizki Sista (Fakultas Tarbiyah, Universitas Darussalam Gontor, 2017)
The purpose of this research are to explore the student’s comprehension of Islamic knowledge in the high school or similar institution in Pronorogo, to explore the teenager moral’s quality in the high school or similar institution in Ponorogo, and to explore the influence of comprehension of Islamic knowledge on teenager moral’s quality in Ponorogo. This research focused on three different institutions, which is the state school, Islamic madrasah schools, and Islamic boarding school known as pesantren. The object of this research is the students on high school’s age period, because in this period, students should has to learn many Islamic knowledge in their school and theirs moral attitude has been built. the result of analysis of research data and r table with N 300 with significance level 5%. The results of data analysis have been able to conclude that the hypothesis in accordance with this research is there is no influence from the understanding of Islamic education materials with the moral development of adolescents in Ponorogo.